Unnatural Amino Acids Methods and Protocols - Pollegioni, Loredano; Servi, Stefano; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Even though they are present in nature, non-proteinogenic amino acids are usually defined as unnatural or non-natural. Beside their structural diversity, interest in these compounds is due to their occurrence in nature, their biological properties, the analytical aspects, their use as probes, and their incorporation into peptides and proteins, among other reasons. Divided into five convenient sections, Unnatural Amino Acids: Methods and Protocols deals with enzymatic methods used to produce non-natural amino acids, aspects concerning the presence of  unnatural amino acids in peptides with antimicrobial properties, genetic  incorporation of unnatural amino acids into proteins (yeast and mammalian cells), and detection and quantification of D-amino acids and related enzymes. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible, Unnatural Amino Acids: Methods and Protocols serves as an ideal guide for scientists and contributes to directing the attention of researchers to the many fields of growing scientific interest in non-natural amino acids.
Preparation of Unnatural Amino Acids with Ammonia-lyases and 2,3-aminomutases -- Multistep Enzyme Catalyzed Reactions for Unnatural Amino Acids -- Enzymatic Production of Enantiopure Amino Acids from Mono-substituted Hydantoin Substrates -- Preparation of Glutamate Analogues by Enzymatic Transamination -- Carbon-Carbon Bond Forming Enzymes for the Synthesis of Non-natural Amino Acids.-  Engineering Cyclic Amidases for Non-natural Amino Acid Synthesis -- NMR Analysis of Unnatural Amino Acids in Natural Antibiotics -- Site-specific Incorporation of Unnatural Amino Acids as Probes for Protein Conformational Changes -- Application of Unnatural Amino Acids to the De novo Design of Selective Antibiotic Peptides -- Use of Unnatural Amino Acids to Probe Structure-activity Relationships and Mode-of-action of Antimicrobial Peptides -- Experimental Methods for Scanning Unnatural Amino Acid Mutagenesis -- Genetic Incorporation of Unnatural Amino Acids into Proteins in Yeast -- Site-specific Incorporation of Unnatural Amino Acids into Proteins in Mammalian Cells -- Incorporation of Unnatural Non-a-amino Acids into the N-terminus of Proteins in a Cell-free Translation System -- Site Specific Modification of Proteins by the Staudinger-phosphite Reaction -- HPLC Methods for Determination of D-aspartate and N-methyl-D-aspartate -- Estimation of Chronological Age from the Racemization Rate of L- and D-aspartic Acid: How to Completely Separate Enantiomers from Dentin -- Enzymatic Detection of D-amino Acids -- An Enzymatic-HPLC Assay to Monitor Endogenous D-serine Release from Neuronal Cultures -- Electrophysiological Analysis of the Modulation of NMDA-receptors Function by d-serine and Glycine in the Central Nervous System -- Biosensors for D-amino Acid Detection -- Analysis of D-β-aspartyl Isomers at Specific Sites in Proteins -- Nutritional Value of D-amino Acids, D-peptides and Amino Acid Derivatives in Mice -- Preparation and Assay of Recombinant Serine Racemase -- Assay of Amino Acid Racemases -- Assays of D-amino Acid Oxidases -- Enzymes Acting on D-amino Acid Containing Peptides.
Keywords: Biochemistry; Enzymology; Biochemistry, general; Enzymology